Improved Low Voltage Ride through Capability of a Fixed Speed Wind Generator Using Dynamic Voltage Restorer. (2016) - Sebastian, Preethi; Nair, Usha
Abstract: Wind energy is one of the fastest growing renewable energy technologies in world. The new grid code proposes that the wind turbine should remain connected to the grid during voltage disturbances. Three phase voltage sags and faults cause reduction in voltage at the point of interconnection to the grid when fixed speed wind turbines connected to squirrel cage induction generators are employed resulting in disconnection of wind turbine from the grid. Dynamic voltage restorer is a series connected custom power device used for voltage compensation during sags and swells. In this paper, the Low voltage ride through capability of a fixed speed wind turbine is improved using dynamic voltage restorer. Simulation studies are done to determine the transient stability of a fixed speed wind turbine with squirrel cage induction generator using Matlab Simulink.